Population exposure to smoking and tobacco branding in the UK reality show ‘Love Island’ - Barker, Alexander B.; Opazo-Breton, Magdalena; Cranwell, Joanne; Britton, John; Murray, Rachel L. (BMJ Publishing Group, 2018)
Background: Reality television shows are popular with children and young adults; inclusion of tobacco imagery in these programmes is likely to cause smoking in these groups. Series 3 of the UK reality show Love Island, broadcast in 2017, attracted widespread media criticism for high levels of smoking depicted. We have quantified this tobacco content and estimated the UK population exposure to generic and branded tobacco imagery generated by the show.